Success of Dental Implants Towards Diabetes Mellitus Patients – A Review - Shalini S, Priscilla; S, Bhuminathan; Kumar, Ajitha Suresh (Journal of Neonatal Surgery, 2025)
In recent times, the rising global prevalence of diabetes has emerged as a notable societal worry. Among individuals with diabetes, persistent hyperglycemia over the long term has the potential to impact the human body system. Diabetes has been recognized for its negative impact on oral rehabilitation. specifically affecting the process and outcomes of dental implant procedures. Since 1990, there have been extensive studies conducted and published concerning osseointegration and the outlook for dental implants among individuals with diabetes. Diabetes on dental implant success has been comprehensively examined in this research, and variables that might enhance osseointegration. Research indicates that dental implants can remain viable in diabetic patients. Implant failure rates are significant, according to research on diabetic animals and the literature. Even in individuals with moderately uncontrolled diabetes, most clinical investigations show that the dental implants failure is statistically negligible. The clinical outcomes of implants in diabetic patients seems to be comparable to that of those without diabetes when appropriate treatment planning, preventative measures, and post-operative care are taken